Editorial - Severgnini, Hernán; García, Pío; Velasco, Marisa; Salvatico, Luis; Venturelli, Alfonso Nicolás (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2019)
Editorial para el volumen, 3 número 2, de EHC.